Quantum reflection of atoms induced by a Feshbach resonance in the atom-surface potential - Wong, Cheng Yi (Nanyang Technological University, 2022)
In this final year project thesis, I outline a method to calculate the reflection probability induced by Feshbach resonance between the ground state and the excited state of an atom in an atom surface potential. The eigenstates and eigen-energies of the atom-surface potential are calculated using the Wentzel-Kramers-Brillouin method. The reflection coefficient, as derived from scattering theory, is then calculated with the integrals in the expression solved numerically. An example calculation is performed to demonstrate the method with the assumption that the optical field the atom experiences is constant.